Erratum: Shifrin O.S. et al., “Russian Non Interventional Study of the Efficacy and Tolerability of Rifaximin Therapy in Patients with Uncomplicated Diverticular Disease under the Conditions of Outpatient Practice” - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
.